Epidemiology of Interpersonal Trauma among Women and Men Psychiatric Inpatients: A Population-Based Study. (February 2020) - Gatov, Evgenia; Koziel, Nicole; Kurdyak, Paul; Saunders, Natasha R.; Chiu, Maria; Lebenbaum, Michael; Chen, Simon; Vigod, Simone N.
Objective: Small clinical samples suggest that psychiatric inpatients report a lifetime history of interpersonal trauma. Since past experiences of trauma may complicate prognosis and treatment trajectories, population-level knowledge is needed about its prevalence and correlates among inpatients. Methods: Using health-administrative databases comprising all adult psychiatric inpatients in Ontario, Canada (2009 to 2016, n = 160, 436, 49% women), we identified those who reported experiencing physical, sexual, and/or emotional trauma in their lifetime, 1 year, and 30 days preceding admission. We described the prevalence of each type of trauma, comparing women and men using modified Poisson regression, and identified individual-level characteristics associated with lifetime trauma history using multivariable logistic regression. Results: 31.7% of inpatients reported experiencing trauma prior to admission. Lifetime prevalence was higher in women (39.6% vs. 24.1%; age-adjusted prevalence ratio [aPR] = 1.68; 95% CI, 1.65 to 1.71), including sexual (22.7% vs. 8.4%; aPR = 2.81; 95% CI, 2.73 to 2.89), emotional (33.3% vs. 19.4%; aPR = 1.76; 95% CI, 1.72 to 1.79), and physical trauma (24.2% vs. 14.8%; aPR = 1.68; 95% CI, 1.65 to 1.72). Factors most prominently associated with lifetime trauma were witnessing parental substance use (adjusted odds ratio [aOR] = 8.68; 95% CI, 8.39 to 8.99), female sex (aOR = 2.29; 95% CI, 2.23 to 2.35), and number of recent stressful life events (aOR = 1.62; 95% CI, 1.59 to 1.65). Conclusions: These results suggest that trauma-informed approaches are essential to consider in the design and delivery of inpatient psychiatric services for both women and men.